First Experiences with Fusion of PET-CT and MRI Datasets for Navigation-Assisted Percutaneous Biopsies for Primary and Metastatic Bone Tumors - Hagen Fritzsche; Alexander Pape; Klaus-Dieter Schaser; Franziska Beyer; Verena Plodeck; Ralf-Thorsten Hoffmann; Patricia Hahlbohm; Elisabeth Mehnert; Anne Weidlich (Diagnostics)
Background: The aim of this study was to compare the technique of navigation-assisted biopsy based on fused PET and MRI datasets to CT-guided biopsies in terms of the duration of the procedure, radiation dose, complication rate, and accuracy of the biopsy, particularly in anatomically complex regions. Methods: Between 2019 and 2022, retrospectively collected data included all navigated biopsies and CT-guided biopsies of suspected primary bone tumors or solitary metastases. Navigation was based on preoperative CT, PET-CT/-MRI, and MRI datasets, and tumor biopsies were performed using intraoperative 3D imaging combined with a navigation system. Results: A total of 22 navigated (main group: m/f = 10/12, mean age: 56 yrs.) and 57 CT-guided biopsies (reference group: m/f = 36/21, mean age: 63 yrs.) were performed. Patients were grouped according to anatomic sites (pelvis, spine, extremities, thorax). The duration of the procedure in the reference group was significantly shorter than in the main group, particularly in the spine. The effective radiation dose was in the same range in both groups (main/reference group: 0.579 mSv and 0.687 mSv, respectively). In the reference group, a re-biopsy had to be performed in nine patients (diagnostic yield: 84%). A total of four major and three minor complications occurred in the reference group. Conclusions: Navigation-assisted percutaneous tumor biopsy resulted in correct, histologically useable diagnoses in all patients and reached a higher accuracy and first-time success rate (diagnostic yield: 100%) in comparison to CT-guided biopsies. The fusion of PET, CT, and MRI datasets enables us to combine anatomical with metabolic information. Consequently, target selection was improved, and the rate of false negative/low-grade sampling errors was decreased. Radiation exposure could be kept at a comparable level, and the durations of both procedures were comparable to conventional methods.